PENGEMBANGAN SELIMUT EMERGENCY STRETCHER BLANKET SEBAGAI UPAYA PENCEGAHAN HIPOTERMIA PADA KORBAN TRAUMA - Siska Ayu Setya Ningrum; Agus Khoirul Anam; Mujito .; Andi Hayyun Abiddin (Jurnal Kesehatan Mesencephalon, 2021)
Emergency Stretcher Blanket is an innovation blanket product that was modified for victims to be transported using a stretcher from the scene to the ambulance or hospital. The function of the Emergency Stretcher Blanket product is to maintain the victim's body temperature remains optimal and prevent the risk of hypothermia during the victim's transportation process. The purpose of this research is to identify the development process and identify the feasibility of the Emergency Stretcher Blanket product. This study used Research and Development design with adopted ADDIE development model which consists of five stages including analysis, design, development, implementation and evaluation. This research was conducted in Gedog Village, Sananwetan District, Blitar City with 7 respondents consisting of 6 KELTANA cadres and 1 expert validator. The results of this study indicate that the Emergency Stretcher Blanket product meets the appropriate criteria to be used based on the assessment of expert validators and respondents. It is expected that the Emergency Stretcher Blanket product can help KELTANA Gedog cadres as an alternative use option to facilitate the evacuation of victims and prevent hypothermia in trauma victims.